Analisis Geomorfologi Daerah Jampang Tengah dan Sekitarnya, Kabupaten Sukabumi, Provinsi Jawa Barat - Muhammad Astridho Arsyad; Idarwati; Muhammad Alfath Salvano Salni (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
The geomorphological analysis of the Jampang Tengah area, Sukabumi Regency, West Java, aims to identify the ongoing geomorphological processes and geomorphic units within the study area. Based on its geographical location, the study area is part of the Bogor Basin, which is characterized by relatively unique geological settings in terms of stratigraphy, geological structure, and geomorphology. The geomorphic units were identified through several aspects, including morphological (physical) aspects consisting of morphography and morphometry, as well as morphodynamic aspects. The research was conducted using field observation methods and studio analysis based on Geographic Information Systems (GIS). The research process began with preliminary identification through the interpretation of Digital Elevation Model (DEM) data, which was correlated with field features through direct observations from various strategic points. Supporting phenomena were described and measured to collect geomorphological data. The identified geomorphic units in the study area include Highly Eroded Denudational High Hills, Moderately Eroded Denudational High Hills, Fault Zone High Hills, Synclinal Hills, and Karst Hills. These geomorphic units can be utilized as information for further studies, disaster mitigation support data, and regional development planning.